On Finite A-Groups with Complementable Nonmetacyclic Subgroups - Baryshovets, P. P. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We study groups G satisfying the following conditions: (i) G is a finite solvable group with nonidentity metacyclic second derived subgroup; (ii) all Sylow subgroups of G are Abelian, but not all of them are elementary Abelian. We give a description of the structure of such groups with complementable nonmetacyclic subgroups.